An application of asset based community development approach: a case study from rural community in Egypt - Hessin, Alyaa Farouk (AUC Knowledge Fountain, 2015)
Many communities in Egypt, specifically the rural areas, are unquestionably distressed places as a result of the major economic and political shifts that have occurred over the past few years. Strategies of community development are currently viewed as the radical remedy for poverty related problems. In Egypt, community development strategies are usually driven from traditional approaches including charity, needs and rights based approaches which focus on basic needs like shelters and food. These approaches have proved a deficiency as they ignore the structural causes of poverty and address symptoms only. In response to these shortages came an alternative capacity focused practice called Asset Based Community Development (ABCD) approach. The case in this research is that ABCD could offer a coherent strategy of sustainable development in poor communities in Egypt. Based on that, the main objectives of the research is to study the application of ABCD approach in rural areas, and in turn present a customized ABCD approach derived from the international guidelines and the Egyptian experience. In order to fulfill these objectives, case studies from the rural communities in Egypt that adopts ABCD approach were extensively studied mostly through qualitative research methods. The analysis and the findings of the current research are most relevant to developing countries and to those emerging from state capitalism and centralization. The results of the research give substantial contribution in understanding and identifying the ABCD approach. Thus, a possible way is paved to generalize this bottom up development strategy over poor communities.